A Research Synthesis of Therapeutic Interventions for Whiplash-Associated Disorder: Part 1 – Overview and Summary - Robert W Teasell; J Andrew McClure; David Walton; Jason Pretty; Katherine Salter; Matthew Meyer; Keith Sequeira; Barry Death (Pain Research and Management)
Whiplash-associated disorder (WAD) represents a significant public health problem, resulting in a substantial socioeconomic burden throughout the industrialized world, wherever costs are documented. While many treatments have been advocated for patients with WAD, scientific evidence of their effectiveness is often lacking. A systematic review was conducted to evaluate the strength of evidence supporting various WAD therapies. Multiple databases (including Web of Science, EMBASE and PubMed) were searched to identify all studies published from January 1980 through March 2009 that evaluated the effectiveness of any clearly defined treatment for acute (less than two weeks), subacute (two to 12 weeks) or chronic (longer than 12 weeks) WAD. The present article, the first in a five-part series, provides an overview of the review methodology as well as a summary and discussion of the review’s main findings. Eighty-three studies met the inclusion criteria, 40 of which were randomized controlled trials. The majority of studies (n=47) evaluated treatments initiated in the chronic stage of the disorder, while 23 evaluated treatments for acute WAD and 13 assessed therapies for subacute WAD. Exercise and mobilization programs for acute and chronic WAD had the strongest supporting evidence, although many questions remain regarding the relative effectiveness of various protocols. At present, there is insufficient evidence to support any treatment for subacute WAD. For patients with chronic WAD who do not respond to conventional treatments, it appears that radiofrequency neurotomy may be the most effective treatment option. The present review found a relatively weak but growing research base on which one could make recommendations for patients at any stage of the WAD continuum. Further research is needed to determine which treatments are most effective at reducing the disabling symptoms associated with WAD.